2016
DOI: 10.3177/jnsv.62.281
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of δ-Tocotrienol and Ferulic Acid Synergistically Inhibits Telomerase Activity in DLD-1 Human Colorectal Adenocarcinoma Cells

Abstract: Summary Rice bran is a rich source of functional compounds, including tocotrienol (T3) and ferulic acid (FA). We previously investigated the anti-cancer properties of T3, and reported on the potent inhibitory effects of d-T3 on angiogenesis and telomerase activity. In this study, we examined the synergistic suppressive effects of the combination of d-T3 and FA on telomerase activity in DLD-1 human colorectal adenocarcinoma cells. Co-treatment with d-T3 and FA significantly decreased cellular telomerase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The anti-neoplastic effects of T3 have been extensively studied using tumor cells of mammary gland [351][352][353][354][355][356], lung [357][358][359][360][361][362], liver [363][364][365][366][367] pancreas [368], prostate [362,[369][370][371][372], cervix [373,374], skin [362,[375][376][377], brain [357][358][359]378], stomach [379], and colon [378,380]. Besides that, T3 tends to accumulate in the liver and pancreatic tissues as well as tumor tissues with an unknown mechanism [367,381].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…The anti-neoplastic effects of T3 have been extensively studied using tumor cells of mammary gland [351][352][353][354][355][356], lung [357][358][359][360][361][362], liver [363][364][365][366][367] pancreas [368], prostate [362,[369][370][371][372], cervix [373,374], skin [362,[375][376][377], brain [357][358][359]378], stomach [379], and colon [378,380]. Besides that, T3 tends to accumulate in the liver and pancreatic tissues as well as tumor tissues with an unknown mechanism [367,381].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…It was recently, reported that T3 controls the synthesis and metabolism of intrinsic sphingolipids, including GlcCer, in the colon and pancreatic cancer cells in vitro 23,24 . Additionally, when both T3 and free FA are added to the colon and pancreatic cancer cells in vitro, intracellular T3 concentrations are higher than when T3 is added alone 25,26 . This increases the apoptotic effects on cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, in another study, the same researchers demonstrated that the combination of FA and δ-T3 significantly decreases cellular telomerase activity in colorectal adenocarcinoma cells. Moreover, it was thought that FA increases the bioavailability of δ-T3 (46). In a study conducted with breast cancer cells, it was shown that FA renders cancer cells more hypersensitive to ABT-888, poly In this study, to demonstrate the efficacy of FA in combination therapy, a combination dose was primarily determined considering the IC 50 doses of FA and gemcitabine.…”
Section: Discussionmentioning
confidence: 99%